SARS-Cov-2 airborne transmission in closed spaces - Huayanay, Leandro (2020)
Transmission of SARS-Cov-2 in the current pandemic is assumed to be through small heavy droplets that quickly fall to the ground, do not stray far from the emitter, however episodes of super- spreading in closed environments, and current studies that they show that when speaking, a patient can produce a large number of small drops that are suspended for up to a quarter of an hour, which would make air transmission possible, should be taken into account when restarting activities , improving ventilation and avoiding crowds in closed spaces.